2010
DOI: 10.1007/s11481-010-9198-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulated Antiretroviral Drug Combinations Extend Drug Release and Antiretroviral Responses in HIV-1-Infected Macrophages: Implications for NeuroAIDS Therapeutics

Abstract: We posit that improvements in pharmacokinetics and biodistributions of antiretroviral therapies (ART) for human immunodeficiency virus-type one infected people can be achieved through developments in nanoformulations. To this end, we manufactured nanoparticles of atazanavir, efavirenz, and ritonavir (termed nanoART) and treated human monocyte-derived macrophages (MDM) in combination therapies. This resulted in improved drug uptake, release and antiretroviral efficacy over monotherapy. MDM rapidly, within minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 42 publications
4
89
0
Order By: Relevance
“…Cells were exposed to native ATV or nanoATV for 24 h at 30 and 70 g/ml for each treatment. Previous studies in our laboratory had shown that these concentrations of native and nanoATV are not toxic to MDM (5,6). Substantial (about 3 orders of magnitude) differences were observed in the rate and extent of drug uptake between the native and nanoATV treatment groups (Fig.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Cells were exposed to native ATV or nanoATV for 24 h at 30 and 70 g/ml for each treatment. Previous studies in our laboratory had shown that these concentrations of native and nanoATV are not toxic to MDM (5,6). Substantial (about 3 orders of magnitude) differences were observed in the rate and extent of drug uptake between the native and nanoATV treatment groups (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…This is seen in nanoART's abilities to maintain consistent plasma and tissue drug levels, as demonstrated in our previous studies (4). Nonetheless, to facilitate clearance of human immunodeficiency virus type 1 (HIV-1), antiretroviral drugs need to be effectively delivered to viral sanctuaries (5). This can target persistent or restricted infection (6)(7)(8).…”
mentioning
confidence: 85%
“…12 Cell supernatant samples (10 µL) were mixed with 10 µL of 100 mM Tris-HCl (pH 7.9), 300 mM KCl, 10 mM DTT, and 0.1% nonyl phenoxylpolyethoxylethanol-40 (NP-40) in a 96-well plate. The samples were incubated at 37°C for 15 minutes.…”
Section: Measurement Of Rt Activitymentioning
confidence: 99%
“…The samples were incubated at 37°C for 15 minutes. Twenty-five microliters of a solution containing 50 mM Tris-HCl (pH 7.9), 150 mM KCl, 5 mM DTT, 15 mM MgCl 2 , 0.05% NP-40, 10 µg/mL poly(A), 0.250 U/mL oligo d(T), [12][13][14][15][16][17][18] and 10 µCi/mL 3 H-TTP was then added to each well and incubated at 37°C for 18 hours. Following incubation, 50 µL of ice-cold 10% trichloroacetic acid was added to each well, and the well contents were harvested onto glass fiber filters and assessed for 3 H-TTP incorporation by β-scintillation spectroscopy.…”
Section: Measurement Of Rt Activitymentioning
confidence: 99%
See 1 more Smart Citation